(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The aim of this paper is to enrich the existing research on eco-innovation and to provide an insight into the existing body of literature on eco-innovation determinants by analyzing the most significant publications in the area and the subjects of interest. The research adopts the document analysis method summarising definitions, classifications and recent developments in the area in order to develop insights into the evolution of eco-innovation and its main determinants. The findings are general and should be used by taking into account the specificity and local conditions within each country as well as the distinct environmental areas. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.